Validity and Reliability of a Modified Reactive Agility Test for Tennis Volley Performance - Wisnu Nugroho; Rekyan Woro Mulaksito Mulyadi (MASI Mandiri Edukasi, 2026)
Reactive agility is a critical component of tennis performance, particularly in volley situations that require rapid perceptual-motor responses under time constraints. However, existing agility tests often lack specificity for volley movements, limiting their ability to assess performance accurately. This study aims to examine the validity and reliability of a modified two-direction reactive agility test specifically designed for tennis volley performance. The research employed a quantitative approach using expert judgment and performance testing. Content validity was assessed using Aiken’s V, inter-rater reliability was analyzed using the Intraclass Correlation Coefficient (ICC), and descriptive statistics were used to evaluate performance outcomes. The results showed that all test components achieved high validity, with Aiken’s V values ranging from 0.83 to 0.96, indicating strong agreement among experts. Reliability analysis revealed ICC values of 0.68 for single measures and 0.88 for average measures, indicating moderate to high reliability. Descriptive findings indicated consistent and rapid execution times, reflecting the specific demands of volley performance. In conclusion, the modified reactive agility test is a valid and reliable instrument for assessing tennis volley performance and is practical for training and evaluation.